134k views
5 votes
Write the quadratic function f(x) = 3x2 - 6x + 9 in vertex form. A) f(x) = 3(x - 3)2 + 9 B) f(x) = 3(x - 1)2 + 6 C) f(x) = 3(x + 3)2 + 6 D) f(x) = 3(x + 1)2 + 9

User Hungerstar
by
5.0k points

1 Answer

2 votes

Answer:

Option B
f(x)=3(x-1)^(2)+6

Explanation:

we have


f(x)=3x^(2) -6x+9

Group terms that contain the same variable, and move the constant to the opposite side of the equation


f(x)-9=3x^(2) -6x

Factor the leading coefficient


f(x)-9=3(x^(2) -2x)

Complete the square. Remember to balance the equation by adding the same constants to each side


f(x)-9+3=3(x^(2) -2x+1)


f(x)-6=3(x^(2) -2x+1)

Rewrite as perfect squares


f(x)-6=3(x-1)^(2)


f(x)=3(x-1)^(2)+6 ------> equation in vertex form

the vertex is the point
(1,6)

User Sdwilsh
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.